Using Bitcoin Pricing Data to Create a Profitable Algorithmic Trading Strategy - S, Prince Nathan; Saudagar, Onkar (Research Parks Publishing LLC, 2022)
Crypto currency has drastically increased its growth in recent years and Bitcoin(BTC)is a very popular type of currency among all the other types of crypto currencies which is been used in most of the sectors nowadays for trading, transactions, bookings etc. In this paper, we aim to predict the change in bitcoin prices by using machine learning techniques on data from Investing.com. We interpret the output and accuracy rate using various machine learning models. To see whether to buy or sell the bitcoin we created exploratory data analysis from a year of data set and predict the next 5 days change using machine learning models like logistic Regression, Logistic Regression with PCA (Principal Component Analysis) and Neural network.